Organizational Culture in the Digital Workplace: A Bibliometric Review - Loso Judijanto (Westscience Press, 2026)
This paper explores the evolving relationship between organizational culture and digital transformation through a bibliometric review of the existing literature. The study aims to map the key research themes, trends, and emerging gaps in the field, focusing on how digital technologies are reshaping organizational culture, leadership, and employee engagement. By conducting a bibliometric analysis of academic articles published in the last two decades, this review identifies